How Do Anxiety and Relationship Factors Influence the Application of Childbirth Education Strategies During Labor and Birth: A Bowen Family Systems Perspective - Sutcliffe KL; Levett K; Dahlen HG; Newnham E; MacKay LM (Dove Medical Press, 2023)
Kerry L Sutcliffe,1 Kate Levett,1- 3 Hannah G Dahlen,4 Elizabeth Newnham,5 Linda M MacKay6 1School of Medicine, University of Notre Dame Australia, Sydney, NSW, Australia; 2Adjunct Fellow, NICM Health Research Institute, and THRI, Western Sydney University, Sydney, NSW, Australia; 3Honorary Fellow, Centre for Midwifery, Child and Family Health, University of Technology Sydney, Sydney, NSW, Australia; 4School of Nursing & Midwifery, Western Sydney University, Sydney, NSW, Australia; 5School of Nursing & Midwifery, University of Newcastle, Newcastle, NSW, Australia; 6School of Arts & Sciences, University of Notre Dame Australia, Sydney, NSW, AustraliaCorrespondence: Kerry L Sutcliffe, School of Medicine, University of Notre Dame Australia, Auburn Clinical School, 88-90 Water Street, Auburn, Sydney, NSW, 2144, Australia, Tel +61 451771723, Email kerry.sutcliffe@nd.edu.auAbstract: The effectiveness of childbirth education (CBE) has long been debated with studies showing contradictory outcomes for mothers and babies. Understanding how what is learned in CBE is translated into practice during labor and birth is an area that requires investigation as this may be a mediating factor in its effectiveness. Bowen family system theory's concept of differentiation of self, the ability to be guided by and to act from one's beliefs and values, is an organizing principle that may affect how relational factors affect the use and application of CBE at the time of birth. The ability to act with emotional maturity when faced with a stressor, such as childbirth, depends on an individual's capability to separate thoughts from the more reactive feeling process. Recognizing how one's level of differentiation interacts with the anxious responses of others may assist pregnant women and birth partners to make decisions more objectively about how they want to manage the birthing process. For the health professional, understanding the interplay of relationship variables, physiological stress, anxiety and individual reactivity may allow for the provision of more thoughtful evidence-based practice, which may increase objectivity, and aid communication and decision-making for women during birth. Bowen theory, as a comprehensive systems-based approach to understanding human functioning under stress, offers a novel approach to exploring the application of CBE during birth.Keywords: antenatal education, Bowen family systems, anxiety, human functioning, birth partner, relationship factors